Field and laboratory perspectives on fentanyl and carfentanil decontamination - Lindén, Pernilla; Mörén, Lina; Qvarnström, Johanna; Forsgren, Nina; Engdahl, Cecilia Springer; Engqvist, Magnus; Henych, Jiri; Tengel, Tobias; Österlund, Lars; Thors, Lina; Larsson, Andreas; Johansson, Susanne (Scientific reports, 2024)
Abuse of the highly toxic compound fentanyl and its analogues is increasing, raising serious public health concerns due to their potency and availability. Therefore, there is a need for decontamination methodologies to safely remove fentanyl to avoid harmful exposure. In this study, the efficacy of commercial and in-house synthesized decontamination agents (Dahlgren Decon, RSDL (Reactive Skin Decontamination Lotion), FAST-ACT (First applied sorbent treatment against chemical threats), GDS2000, alldecont MED, bleach, Domestos Spray Bleach, Effekt Klor, MgO, TiO2-nanodiamond, and CeO2) were evaluated for the degradation of fentanyl and carfentanil under controlled laboratory conditions and on wooden floor surfaces. Liquid chromatography/mass spectrometry analysis showed that oxidative decontamination agents were the most effective, with N-oxides identified as major degradation products. The physiological effects of these N-oxides were also investigated regarding their ability to activate the µ-opioid receptor and their metabolism in human liver microsomes. The results provide empirical evidence that complements prior research findings on the degradation of fentanyl and carfentanil using a variety of decontamination agents.
Keywords: jaterní mikrozomy; receptory opiátové mu; dekontaminace; Humans; lidé; opioidní analgetika; Fentanyl; Receptors, Opioid, mu; Analgesics, Opioid; fentanyl; Microsomes, Liver; Decontamination